Genome-wide and expression analysis of B-box gene family in pepper - Jing Ma; Jia-xi Dai; Xiao-wei Liu; Duo Lin (BMC Genomics, 2021)
Abstract Background BBX transcription factors are a kind of zinc finger transcription factors with one or two B-box domains, which partilant in plant growth, development and response to abiotic or biotic stress. The BBX family has been identified in Arabidopsis, rice, tomato and some other model plant genomes. Results Here, 24 CaBBX genes were identified in pepper (Capsicum annuum L.), and the phylogenic analysis, structures, chromosomal location, gene expression patterns and subcellular localizations were also carried out to understand the evolution and function of CaBBX genes. All these CaBBXs were divided into five classes, and 20 of them distributed in 11 of 12 pepper chromosomes unevenly. Most duplication events occurred in subgroup I. Quantitative RT-PCR indicated that several CaBBX genes were induced by abiotic stress and hormones, some had tissue-specific expression profiles or differentially expressed at developmental stages. Most of CaBBX members were predicated to be nucleus-localized in consistent with the transient expression assay by onion inner epidermis of the three tested CaBBX members (CaBBX5, 6 and 20). Conclusion Several CaBBX genes were induced by abiotic stress and exogenous phytohormones, some expressed tissue-specific and variously at different developmental stage. The detected CaBBXs act as nucleus-localized transcription factors. Our data might be a foundation in the identification of CaBBX genes, and a further understanding of their biological function in future studies.